2012
DOI: 10.4132/koreanjpathol.2012.46.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bronchiolar and Alveolar Cell Injuries Induced by Short- and Long-term Exposure to Sidestream Smoke

Abstract: BackgroundWe investigated effects of short- and long-term exposure to sidestream smoke on the bronchiolar and alveolar cells in Sprague-Dawley rats.MethodsRats were divided into five experimental groups: groups 1, 2, and 3 (1-month exposure to 3, 5, and 7 cigarettes a day, respectively), groups 4 and 5 (3- and 6 month exposure to five cigarettes a day, respectively). We examined the morphologic changes, the expressions of tumor necrosis factor α (TNF-α), tumor growth factor β1 (TGF-β1), interlekin (IL)-1α, IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Magnani et al (2012) described changes in the lung tissue corresponding to those we observed in this study, in particular, degenerative changes of alveolocytes, as well as the presence of thin, disorganized collagen fibrils in the interalveolar membranes with the formation of aggregates (bundles) in various areas of the interstitium [13]. According to a study by Kwon et al (2012), exposure to varying volumes of tobacco smoke can cause similar changes in the respiratory tract of experimental animals. These changes include a decrease in the number of epithelial cells, destruction of these cells, uneven distribution of secretory granules, and thickening of the bronchial walls [16].…”
Section:  Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Magnani et al (2012) described changes in the lung tissue corresponding to those we observed in this study, in particular, degenerative changes of alveolocytes, as well as the presence of thin, disorganized collagen fibrils in the interalveolar membranes with the formation of aggregates (bundles) in various areas of the interstitium [13]. According to a study by Kwon et al (2012), exposure to varying volumes of tobacco smoke can cause similar changes in the respiratory tract of experimental animals. These changes include a decrease in the number of epithelial cells, destruction of these cells, uneven distribution of secretory granules, and thickening of the bronchial walls [16].…”
Section:  Discussionsupporting
confidence: 69%
“…According to a study by Kwon et al (2012), exposure to varying volumes of tobacco smoke can cause similar changes in the respiratory tract of experimental animals. These changes include a decrease in the number of epithelial cells, destruction of these cells, uneven distribution of secretory granules, and thickening of the bronchial walls [16]. Excessive collagenization can be seen as an early sign of exposure to tobacco smoke, which can later lead to pulmonary fibrosis.…”
Section:  Discussionmentioning
confidence: 99%